Role of Self-Efficacy Toward Students’ Achievement in Mathematical Multiple Representation Ability (MMRA) - Fonna, Mutia; Mursalin, Mursalin (Jurnal Ilmiah Peuradeun, 2018)
Various studies showed that there are some points which affect students’ achievement; one of them is mathematics self-efficacy. Self-efficacy is feeling, trust, and confidence of affective behavior of students toward their ability. In learning process, the students find obstacles in solving their problem such as relating one representation to another representation. Previous studies indicated that students’ achievement of mathematical representation ability have obstacles because the students did not understand relationship between concepts, ideas, and materials to be represented. The other studies claimed that the higher students’ self-efficacy, the higher mathematical multiple representation ability (MMRA). It means that self-efficacy has positive correlation with mathematic ability. This article will discuss about role of mathematics self-efficacy toward ability achievement of mathematical multiple representation ability (MMRA) in solving mathematics problem in order to increase students’ achievement.